QiṢāṢ Pada Tindak Pembunuhan; Konsep Dan Praktik Pada Masa Nabi Muhammad SAW - Bahrul Fawaid (SOSIO DIALEKTIKA : JURNAL ILMU SOSIAL HUMANIORA, 2020)
Abstract This study aims to explain the basic concepts of qiṣāṣ in acts of murder in Islamic law and the practices of qiṣāṣ in acts of murder during the time of the Prophet Muhammad. The relation between these two things becomes the main discussion of this research. This research is a normative / doctrinal legal research, with statute aproach and historical approach. The study results showed that first, qiṣāṣ is a standard rule of Islamic law sourced from the Qur'an and hadith, and is prescribed to be a deliberate resolution of torture or murder. Qiṣāṣ is a form of punishment imposed on perpetrators of crime, which is similar to what he has done to the victim. Secondly, during the time of the Prophet Muhammad, there were several murder cases. Among these cases, some were resolved by the qiṣāṣ mechanism, some were resolved by a forgiveness mechanism, that is, when the victim's family forgave the perpetrator and did not demand the perpetrator to be punished by qiṣāṣ. It can be illustrated that indeed qiṣāṣ is a thing prescribed in Islam, but in practice, acts of killing are not always resolved by qiṣāṣ. The case position, principle of expediency, and fairness are considered in determining the best solution for all parties.